PENERAPAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK (Studi Tentang Penerapan Diversi Di Wilayah Pengadilan Negeri Klaten) - WAHYUNINGSIH, IRMA (Dinamika Hukum, 2015)
Diversion is the provision authorizes law enforcement officers to take measures wisdom in handling or resolving the violation of children by not taking a formal include a stop or discontinue or release of the criminal justice process or to return or hand over to the public and other forms of service activities other social. The research objective was to examine the role and the diversion of children in conflict with the law based on the Constitution of the Republic of Indonesia Number 11 of 2012 on the Criminal Justice System Child and assess the stages after the process of diversion successful until the rising of the determination of the diversion of the Chairman of the Court Klaten and obstacles in the implementation of diversion. The research method is a combination of normative and empirical, which examines the legal norms and also observe the implementation of the Law of the Republic of Indonesia Number 11 of 2012 on the Criminal Justice System Child, research methods based on the specification of the research and data collection tools. The results of the research that the diversion is done in the judicial process both at the level of investigation (police), prosecution, and in court (the Court). In the diversion is done through consultations involving children and parents, or his representative, supervisor of social and professional social workers. After the diversion is completed, then the agreement diversion was submitted by the direct supervisor responsible officials at each level of scrutiny to the district court within the legal jurisdiction within a period of three (3) days after the agreement signed diversion, and then issue the determination by the Chairman of the Court. Keywords: Law No. 11 of 2012, Diversion